Analisis Potensi Ekonomi Pertanian Permakultur dan Pengembangannya di Desa Hutabaru Sil, Kec. Dolok, Kabupaten Padang Lawas Utara Perspektif Ekonomi Islam - Suliani Suliani; Zuhrinal M. Nawawi; Budi Dharma (ITB AAS INDONESIA Surakarta, 2023)
The development of a village is one of the important and a concern in every village. With the aim of a village that has competitiveness, the village apparatus and pamong need to pay attention to increasing the economic potential of the village as a local resource. This study aims to find out how the economic and development potential in the village of Huta Baru Sil, Dolok District, North Padang Lawas Regency. The analytical method used in this study is descriptive qualitative analysis through data collection using interview techniques. Descriptive method is a research method by collecting data that is in accordance with the actual data then compiled, processed and analyzed to be able to provide an overview of the problems that exist in the area. Descriptive analysis is a method that is carried out by explaining or describing the actual situation about how the village's potential is developed. In addition, this analysis was carried out by describing secondary data regarding the area of land and permaculture agricultural products that can be produced. The research instrument in qualitative research is the researcher himself who acts as a human instrument that performs the function of setting the research focus, collecting data, interpreting data, interpreting and making conclusions. The informant for this study was Mr. H. Ahmad Saihu Siregar, who was always the owner of permaculture agricultural land. The results of this research are the efforts of landowners and the community in developing village potential through permaculture farming with collaboration between landowners and the local community with the aim of increasing the economy of the Huta Baru Sil village community and providing an example to the people around the village so that they don't only farm oil palm and rubber but can also do permaculture farming with makeshift land to boost the economy. From the results of the permaculture harvest that was carried out starting from 2021-2022 it was very good and the results continued to increase and really helped the income of people who own the land. Based on the data analysis and discussion that has been put forward, it can be concluded that Huta Baru Village has enormous potential in the agricultural sector. The results of identifying the internal and external environmental conditions of the agricultural sector in Huta Baru sil village can be formulated several alternative strategies in developing the agricultural sector in Huta Baru sil, namely as follows: SO strategy (strengths-opportunities) to optimally utilize all existing potentials. The ST strategy (strengths -threats) optimizes farm management. WO strategy (weaknesses - opportunities) sustainable development for farmers. WT strategy (weaknesses-threats) to improve production facilities and trading system..